1999
DOI: 10.1093/oxfordjournals.jbchem.a022564
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Cytogenesis in Adult Rat Adrenal Cortex: Circadian and Zonal Variations and Their Modulation by Adrenocorticotropic Hormone

Abstract: Circadian rhythms and zonal variations in the cell proliferation of adult rat adrenal cortex were studied by following the cells in the DNA-synthesizing stage (S-phase) as assessed by 5-bromo-2'-deoxyuridine incorporation into the cell-nuclei and/or by visualizing proliferating cell nuclear antigen. The S-phase cells were observed throughout the day in two regions of the adrenal cortex: (i) a region from the inner half of the zona glomerulosa to near the outer margin of the zona fasciculata, and (ii) the outer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
4
24
2
Order By: Relevance
“…Since the abundant ACTHR expression was reported in the zona glomerulosa, it is likely that the mitogenic effect of ACTH is a direct action on the cells via ACTHR. It has been demonstrated that there exists a zone containing stem cells between the zona glomerulosa and zona fasciculata in adult rats, especially in Sprague-Dawley rats, which is called the zona intermedia or undifferentiated cell zone (Mitani et al 2003, Vinson 2003, and that cell proliferation in this zone is associated with the circadian rhythm of plasma ACTH levels (Miyamoto et al 1999). Our results are partially compatible with these reports, although the cell proliferation observed in our study is mainly in the zona glomerulosa, but is not confined to the specific zone.…”
Section: Discussionmentioning
confidence: 99%
“…Since the abundant ACTHR expression was reported in the zona glomerulosa, it is likely that the mitogenic effect of ACTH is a direct action on the cells via ACTHR. It has been demonstrated that there exists a zone containing stem cells between the zona glomerulosa and zona fasciculata in adult rats, especially in Sprague-Dawley rats, which is called the zona intermedia or undifferentiated cell zone (Mitani et al 2003, Vinson 2003, and that cell proliferation in this zone is associated with the circadian rhythm of plasma ACTH levels (Miyamoto et al 1999). Our results are partially compatible with these reports, although the cell proliferation observed in our study is mainly in the zona glomerulosa, but is not confined to the specific zone.…”
Section: Discussionmentioning
confidence: 99%
“…This observation supports previous work supporting a role for ACTH in the maintenance of adrenal cortical mass under nonstress conditions. For example, circadian increases in fasciculata cell proliferation that are preceded by increases in plasma ACTH can be blocked by dexamethasone (34), and adrenal atrophy produced by chronic dexamethasone treatment can be prevented (28,40) or reversed (29) by ACTH replacement. In contrast to its suppressive effect in the outer fasciculata, dexamethasone treatment unmasked a proliferative response to unilateral adrenalectomy in glomerulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is absolutely clear that CYP11B2 (aldosterone synthase) is located only in zona glomerulosa cells (Mitani et al 1994, Halder et al 1998, Peters et al 2007 and thus the glomerulosa is undeniably the source of secreted aldosterone, the other steroidogenic enzymes required for aldosterone synthesis are sparse at best in comparison (Vinson 2004), and in any case even in glomerulosa cells, only the outermost contain either CYP11B2 or even StAR (and then only following induction by nephrectomy or high potassium) (Peters et al 1998(Peters et al , 2006. The rest of the glomerulosa is enigmatic, though because of its lack of significant steroidogenic function it has been postulated to be a stem cell population for both glomerulosa and fasciculata cells (Mitani et al 1996, Miyamoto et al 1999, 2001). Here, proof has been elusive, since mitoses can occur throughout the gland (Wright 1971, Horiba et al 1987, McNicol & Duffy 1987, Clark et al 1992, Basile & Holzwarth 1993, Holzwarth 1995, Zieleniewski et al 1995, McEwan et al 1996, Ennen et al 2005, including in the immediate subcapsular region and in the capsule itself (McNeill et al 2005).…”
Section: Discussionmentioning
confidence: 99%